Zika a Vector Borne Disease Detected in Newer States of India Amidst the COVID-19 Pandemic - Yadav, Pragya D.; Kaur, Harmanmeet; Gupta, Nivedita; Sahay, Rima R.; Sapkal, Gajanan N.; Shete, Anita M.; Deshpande, Gururaj R.; Mohandas, Sreelekshmy; Majumdar, Triparna; Patil, Savita; Pandit, Priyanka; Kumar, Abhinendra; et al. (Frontiers in Microbiology, 2022)
Background: During second wave of COVID-19 pandemic, outbreaks of Zika were reported from Kerala, Uttar Pradesh and Maharashtra, India in 2021. The Dengue and Chikungunya negative samples were retrospectively screened to determine the presence of Zika virus from different geographical regions of India. Methods: During May to October 2021, the clinical samples of 1475 patients, across 13 states and a union territory of India were screened and re-tested for Dengue, Chikungunya and Zika by CDC Trioplex Real time RT-PCR. The Zika rRTPCR positive samples were further screened with anti-Zika IgM and Plaque Reduction Neutralization Test. Next generation sequencing was used for further molecular characterization. Results: The positivity was observed for Zika (67), Dengue (121) and Chikungunya (10) amongst screened cases. The co-infections of Dengue/Chikungunya, Dengue/Zika and Dengue/Chikungunya/Zika were also observed. All Zika cases were symptomatic with fever (84%) and rash (78%) as major presenting symptoms. Of them, four patients had respiratory distress, one presented with seizures and one with suspected microcephaly at birth. The Asian Lineage of Zika and all four serotypes of Dengue were found in circulation. Conclusion: Our study indicates the spread of Zika virus to several states of India and an urgent need to strengthen its surveillance.